2007
DOI: 10.1002/cne.21252
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage depletion in the murine olfactory epithelium leads to increased neuronal death and decreased neurogenesis

Abstract: Apoptosis of olfactory sensory neurons (OSNs) induced by olfactory bulbectomy (OBX) leads to the activation of resident macrophages within the olfactory epithelium (OE). These macrophages phagocytose degenerating OSNs and secrete chemokines, which recruit additional macrophages into the OE, and cytokines/growth factors, which regulate basal cell proliferation and differentiation and maturation of OSNs. In this study we apply for the first time the use of liposome-encapsulated clodronate to selectively deplete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 80 publications
4
28
0
Order By: Relevance
“…For example, resident and recruited macrophages have been shown to control survival, degeneration, and replacement of olfactory sensory neurons, another system in which turnover is highly regulated (59). Our data show that OsteoMacs, like macrophages in many other organs (4), occupy a precise anatomical niche and that they are integral to maintenance of osteal tissue homeostasis.…”
Section: Discussionmentioning
confidence: 73%
“…For example, resident and recruited macrophages have been shown to control survival, degeneration, and replacement of olfactory sensory neurons, another system in which turnover is highly regulated (59). Our data show that OsteoMacs, like macrophages in many other organs (4), occupy a precise anatomical niche and that they are integral to maintenance of osteal tissue homeostasis.…”
Section: Discussionmentioning
confidence: 73%
“…This method proved a breakthrough in the study of macrophages, but also showed that, depending on the condition, the effect of the macrophage elimination could be beneficial as well as detrimental. [30][31][32][33][34] The current perception that macrophages are composed of functionally distinct sub-populations, termed M1 and M2, now explains these differential effects and emphasizes the importance of selectively targeting these different sub-populations. During chronic inflammation, there is strong evidence for an inappropriate persistence of M1 macrophages, which are directly associated with the development and perpetuation of many chronic inflammatory and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that combined intranasal and intravenous administration of Lip-C induced a significant 38 and 35% reduction in resident and recruited macrophages in the OE of sham and 48 h OBX mice, respectively (6). Macrophage depletion in the OE resulted in a decrease in OE thickness and the numbers of olfactory marker protein (OMP) ϩ mOSNs and 5-bromo-2-deoxyuridine (BrdU) ϩ proliferating basal cells in sham and 48 h OBX mice.…”
mentioning
confidence: 86%
“…More specifically, recent studies (6,23,33) on the interaction between the immune system and neurogenesis in the OE have strengthened the case for the participation of macrophages in the regulation of OSN survival and the proliferation, differentiation, and maturation of OSN basal progenitor cells in the unperturbed OE and during OE remodeling as a result of olfactory bulbectomy (OBX)-induced OSN apoptosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation